CLAIMS OF SCIENTIFIC APPROACH IN AN ENGLISH LESSON TRANSCRIPT - Munir, Ahmad (Universitas Negeri Surabaya, 2015)
As the generic approach for teaching all subjects in the 2013 Curriculum, five stages of Scientific approach (SA) are subject to adaptation (Permendiknas 103/2014). In response to this, English lessons have married it with genre-based approach (GBA) through stages of instruction, namely building context or knowledge of the field, modeling of text and deconstructing it, joint construction of text, and independent instruction of text. This paper reports an analysis of an English lesson transcript which has been claimed as applying scientific approach in Hafidahs (2014) study. Through a qualitative analysis, all the classroom language used by both teacher and her students were categorized in to their intended five SA stages, GBA stages and their pedagogical intentions (Johnson, 1990). The whole classroom language use was then analysed for its inductive-deductive reasoning. Results show that there is little evidence of scientific approach in that lesson transcript.